Tren Penelitian dan Perkembangan Daging Analog: Analisis Bibliometrik tentang Teknologi Pengolahan dan Keberlanjutan Pasar - Jufrinaldi, Jufrinaldi; Zahran, Rizal Muhammad; Nada, Sayyidah Sofiyah; Wibowo, Muhammad Abdul Malik; Afrozi, Agus Salim; Harwanto, Untung Nugroho; Triandita, Nanda; Faridah, Faridah (Politeknik Negeri Lhokseumawe, 2025)
In the last two decades, research on analog meat and plant-based meat alternatives has undergone significant transformation, driven by advances in science, shifts in consumer behavior, and the growing global urgency regarding the availability of sustainable protein sources. This study presents a systematic bibliometric analysis to identify trends in scientific publications, countries with the most significant contributions, the most productive authors, and the main thematic developments in the field of analog meat. Using a reputable citation database and a structured keyword search approach, scientific publications from 1966 to 2025 were mapped. The findings reveal exponential growth in the number of publications per year, a shift in regional leadership toward Asia and Europe, and the expansion of global collaborative networks. Authors and institutions with the highest citation rates are profiled, along with the identification of prominent research themes such as sustainability, sensory analysis, protein structuring, and precision fermentation. The results of this study are expected to contribute strategically to scientific advancement, industry innovation, and policy formulation that supports the transformation of food systems based on sustainable alternative proteins in the future.